Essays on economic development - "Bhatt, V.V" (New Delhi, 2010)
These essays have wide-ranging themes on different aspects of socio-economic development. All of them were written during the last four decades and some were published in well-known national and international journals like Economic and Political Weekly, International Journal of Development Banking in India, American Economic Review (USA), Bulletin of the Oxford University Institute of Economics and Statistics (UK) and KYKLOS (Europe). Some others were published in the publications of international institutes like United Nations, International Monetary Fund and the World Bank. The context in which these essays were written (as others in author's develop-ment perspectives) is indicated in his latest book Perspectives on Development: Memoirs of a Development Economist (Academic Foundation, 2008).
Keywords: Economic development-India